5‐exo versus 6‐endo Thiyl‐Radical Cyclizations in Organic Synthesis. Issue 11 (12th November 2019) - McCourt, Ruairí; Scanlan, Eoin M.
Abstract: Since the discovery of the radical mediated thiol‐ene and thiol‐yne reactions, these reactions have been employed in an intramolecular manner for the synthesis of sulfur‐containing heterocycles. Although closely related on a mechanistic basis, the thiol‐ene and thiol‐yne cyclization can differ greatly in regioselectivity and product distribution, with the thiol‐ene process being more predictable and thus attracting greater utilization. Herein, we review intramolecular thiyl‐radical addition reactions and the factors leading to the observed regioselectivity in examples in which both the 5‐ exo and 6‐ endo mode of cyclization are feasible. We highlight the applications of these important reactions for organic synthesis in the recent literature. Abstract :